REPRESENTASI ALAM DALAM NOVEL ALTITUDE 3676 TAKHTA MAHAMERU KARYA AZZURA DAYANA: TINJAUAN EKOKRITIK - Kharismadani, Kharismadani; Juanda, Juanda; Hajrah, Hajrah (Fakultas Bahasa dan Sastra Indoensia, 2020)
The purpose of this research is to represent the types of environmental damage that come from humans, and the impact of environmental damage. The approach used in this research is the ecocritical. The research design used is descriptive-qualitative. Data is collected by using documentation technique that is reading and recording objects to be studied. The results of research on the type of environmental damage that comes from humans in the form of, soil pollution, critical land, forest damage, exploitation of biodiversity. And the impact of environmental damage in the form, narrowing of the lake, reduced productive land, and damage to ecosystems.